Improving working memory and pain inhibition in older persons using transcranial direct current stimulation - Deldar, Zoha; Rustamov, Nabi; Blanchette, Isabelle; Piché, Mathieu (Neuroscience research, 2019)
•Anodal tDCS increased pain inhibition in older persons.•Anodal tDCS also improved WM but not NFR inhibition in these participants.•Increased pain inhibition may thus be independant of descending modulation.•Anodal tDCS may be useful to improve WM and pain inhibition in older persons. The aim of the present study was to examine whether transcranial Direct Current Stimulation (tDCS) could enhance working memory and pain inhibition in older persons. Fifteen volunteers (7 women, 8 men; mean ± SD: 64 ± 4.4 y.o.) participated in two tDCS sessions during which an n-back task was performed with two levels of working memory load, while painful stimulation was delivered at the ankle. The experiment included five within-subject counterbalanced conditions (pain alone and 0-back or 2-back with or without pain) performed twice during each session. Compared with the pre-tDCS baseline, anodal tDCS decreased response times and improved pain inhibition by working memory in the 2-back condition (p < 0.01), but not in the 0-back or pain alone conditions, while sham tDCS produced no effect (all p > 0.3). These results indicate that working memory and pain inhibition can be improved by tDCS in older persons.